Breaking the 'Undruggable' Barrier: Nanoparticle-Based Combination Therapy Utilizing Sotorasib and PD-L1 Inhibitor for Treating Non-Small Cell Lung Cancer Patients with KRASG12C Mutations - Hao Hanming; Zhang Hanzhi (BIO Web of Conferences)
Lung cancer is a highly prevalent and lethal type of cancer. Although targeted therapy and immunotherapy have received considerable attention in the treatment of lung cancer, particularly non-small cell lung cancer (NSCLC), there has been limited improvement in the overall recovery and survival rates of lung cancer patients. Thus, there is currently a substantial need for more effective therapies for NSCLC. This study aimed to define a new approach for treating NSCLC by employing a nanoparticle-based strategy for co- delivering PD-L1 inhibitor and a targeted candidate, sotorasib. Sotorasib is a small molecule that specifically and irreversibly inhibits KRASG12C, which is the most prevalent KRAS mutation observed in non-small cell lung cancer (NSCLC). This indicates that the combination of targeted therapy with immunotherapy, resulting in a synergistic impact, holds promise as a potential treatment for NSCLC.